Chlorhexidine gluconate versus povidone iodine at cesarean delivery: a randomized controlled trial. (March 2015) - Kunkle, Cynelle M.; Marchan, Jennifer; Safadi, Sara; Whitman, Stephanie; Chmait, Ramen H.
Abstract Background/Aims: To compare the prevalence of positive bacterial cultures at the cesarean delivery (CD) incision site in patients with pre-operative application of chlorhexidine gluconate (CG) versus povidone iodine (PI). Methods: Women undergoing a scheduled CD at ≥36 gestational weeks were randomly assigned to receive CG or PI. A swab of the incision site was performed at 3 min after disinfectant application and at 18 post-operative hours, and the prevalence of cultures with any detected bacterial growth was compared for the two groups. Results: Of the 60 participants, 33 (55.0%) were in the PI group. There were no differences detected at 3 min, with 9.1% positive in the PI group versus 0% positive in the CG group (p = 0.2499). However, at 18 h, women in the PI group were seven times more likely than women in the CG group to have a positive culture (16/33 [48.5%] versus 3/27 [11.1%], OR = 7.53 [95% CI 1.67–38.83], p = 0.0023). Multivariate logistic regression demonstrated similar results: OR = 7.33 (95% CI 1.77–30.35), p = 0.0060. Conclusion: The prevalence of positive bacterial cultures obtained at the site of the skin incision 18 h after CD was higher in the PI versus the CG group.